Compromised thermal tolerance of cardiovascular capacity in upstream migrating Arctic char and brown trout—are hot summers threatening migrating salmonids?. Issue 1 (4th December 2020) - Mottola, Giovanna; Kristensen, Torstein; Anttila, Katja
Abstract : Arctic char and brown trout have extremely low maximum heart rate and thermal tolerance of the cardiovascular system at the beginning of their upstream migration, which makes them vulnerable for heatwaves. Abstract: Heat waves are threatening fish around the world, leading sometimes to mass mortality events. One crucial function of fish failing in high temperatures is oxygen delivery capacity, i.e. cardiovascular function. For anadromous salmonids, increased temperature could be especially detrimental during upstream migration since they need efficiently working oxygen delivery system in order to cross the river rapids to reach upstream areas. The migration also occurs during summer and early autumn exposing salmonids to peak water temperatures, and in shallow rivers there is little availability for thermal refuges as compared to thermally stratified coastal and lake habitats. In order to shed light on the mechanisms underpinning the capacity of migrating fish to face high environmental temperatures, we applied a physiological and molecular approach measuring cardiovascular capacities of migrating and resident Arctic char ( Salvelinus alpinus ) and brown trout ( Salmo trutta ) in Northern Norway. The maximum cardiovascular capacity of migrating fish was significantly lower compared to the resident conspecifics. The onset of cardiac impairment started only 2°C higher than river temperature, meaning that even a small increase in water temperature may already compromise cardiac function. The migrating fish were also under significant cellular stress, expressing increased level of cardiac heat shock proteins. We consider these findings highly valuable when addressing climate change effect on migrating fish and encourage taking action in riverine habitat conservation policies. The significant differences in upper thermal tolerance of resident and migrating fish could also lead changes in population dynamics, which should be taken into account in future conservation plans.